Community perspectives on the use of regulation and law for obesity prevention in children: A citizens' jury. Issue 5 (May 2017) - Street, Jackie M.; Sisnowski, Jana; Tooher, Rebecca; Farrell, Lucy C.; Braunack-Mayer, Annette J.
Highlights: Globally government action on obesity prevention focuses on parental and individual responsibility. Legislative and fiscal approaches could address obesity but policy-makers fear public backlash. This citizens' jury demonstrates public support for targeted legislative and fiscal approaches. Jurors supported educational approaches in schools, mandatory food-labelling laws and sugar taxes. Abstract: Introduction: Childhood obesity is a significant challenge for public health internationally. Regulatory and fiscal measures propagated by governments offer a potentially effective response to this issue. Fearing public criticism, governments are often reluctant to use such measures. In this study we asked a descriptively representative and informed group of Australians their views on the use of legislation and fiscal measures by governments to address childhood obesity. Methods: A citizens' jury, held in South Australia in April 2015, was asked to consider the question: What laws, if any, should we have in Australia to address childhood obesity? Results: The jury agreed that prevention of obesity was complex requiring multifaceted government intervention. Recommendations fell into the areas of health promotion and education (n = 4), regulation of food marketing (n = 3), taxation/subsidies (n = 2) and a parliamentary enquiry. School-based nutrition education and health promotion and mandatory front-of-pack interpretive labelling of food and drink were ranked 1 and 2 with taxation of high fat, high sugar food and drink third. Conclusion: The recommendations were similar to findings from other citizens' juries held in Australia suggesting that the reticence of decision makers in Australia, and potentially elsewhere, to use legislative and fiscal measures to address childhood obesity is misguided. Supporting relevant informed public discussion could facilitate a politically acceptable legislative approach.